Triclosan antagonises fluconazole activity against Candida albicans - (:unkn) unknown (International Association for Dental Research (IADR), 2011)
Triclosan is a broad-spectrum antimicrobial compound commonly used in oral hygiene products. Investigation of its activity against Candida albicans showed that triclosan was fungicidal at concentrations of 16 mg/L. However, at subinhibitory concentrations (0.5-2 mg/L) triclosan antagonized the activity of fluconazole. Although triclosan induced CDR1 expression in C. albicans, antagonism was still observed in cdr1? and cdr2? strains. Triclosan did not affect fluconazole uptake or alter total membrane sterol content, but did induce the expression of FAS1 and FAS2, indicating that its mode of action may involve inhibition of fatty acid synthesis, as it does in prokaryotes. However, FAS2 mutants did not exhibit increased susceptibility to triclosan and overexpression of both FAS1 and FAS2 alleles did not alter triclosan susceptibility. Unexpectedly, the antagonistic effect was specific for C. albicans under hypha inducing conditions and was absent in the nonfilamentous efg1? strain. This antagonism may be due to the membranotropic activity of triclosan and the unique compostion of hyphal membranes.
Epub October 4th
Keywords: Candida albicans; fluconazole; triclosan